A Long Time Gone: Post‐conflict Rural Property Restitution under Customary Law. Issue 3 (May 2016) - Joireman, Sandra F.; Meitzner Yoder, Laura S.
ABSTRACT: Mass displacement of people due to violence poses a unique set of challenges for property restitution when people return to their homes after a long absence. This is particularly evident in rural areas where the dominant form of land holding is customary tenure. Violence‐induced displacement, unlike voluntary migration, challenges both customary and public legal‐administrative structures. The lack of written documentation of customary holdings and the importance of the support of community leaders means that incorporating returnees back into a community can be easier for those who choose to return, while reclaiming property without physical return is nearly impossible. This article seeks to make three contributions: 1) to note the diversity of return processes after long displacements in terms of timing and demographics; 2) to demonstrate that the nature of the claims people can make on customary tenure systems is at odds with international legal norms on property restitution after displacement; and 3) to introduce a set of observations and questions on how conflict can change customary law. The article is based on fieldwork conducted in Uganda, Liberia and Timor‐Leste, all countries with extended displacement where most of the rural land is held via customary claims.